A Comprehensive Review of Etiological Factors and Preventive Strategies for Hepatocellular Carcinoma - Boopathi.P; Jothimanivannan.C; Nanditha.P; Karthi Keyan.M; Vimal.R (Asian Journal of Pharmaceutical Research and Development, 2025)
Hepatocellular carcinoma (HCC), the most common primary malignancy of the liver, constitutes a significant global health challenge. It predominantly develops in the context of chronic liver disease and cirrhosis. This review outlines the principle etiological factors associated with HCC pathogenesis, including chronic infection with hepatitis B and C viruses, excessive alcohol consumption, metabolic syndrome, and exposure to environmental toxins such as aflatoxins. In addition, it examines evidence-based preventive strategies aimed at reducing HCC incidence and mortality. These include vaccination against hepatitis B, antiviral treatment for chronic hepatitis infections, lifestyle modifications targeting obesity and alcohol use, and implementation of surveillance programs in high-risk populations. A comprehensive understanding of these risk factors and preventive approaches is critical for effective disease control and improved patient outcomes.